In-utero exposure to antiretrovirals and neurodevelopment among HIV-exposed-uninfected children in Botswana. (1st June 2018) - Chaudhury, Sumona; Mayondi, Gloria K.; Williams, Paige L.; Leidner, Jean; Shapiro, Roger; Diseko, Modiegi; Ajibola, Gbolahan; Holding, Penny; Tepper, Vicki; Makhema, Joseph; Petlo, Chipo; Seage, George R.; et al.
Abstract : Objective: Conflicting data exist regarding the impact of in-utero exposure to maternal combination antiretrovirals. We compared neurodevelopmental outcomes between HIV-exposed-uninfected (HEU) children exposed in utero to three-drug combination antiretroviral therapy (ART) vs. zidovudine (ZDV) monotherapy. Design: Prospective study of child neurodevelopment, nested within two cohorts of HIV-infected mothers and their children in Botswana (one observational, one interventional). Methods: The Tshipidi and Mma Bana studies enrolled HIV-infected women during pregnancy and followed their HEU children for 24 months. Mothers took three-drug ART or ZDV during pregnancy. ART-exposed babies were mostly breastfed, and ZDV-exposed were formula-fed. Neurodevelopmental outcomes, measured at 24 months using Bayley Scales of Infant and Toddler Development Third Edition (Bayley-III) and Development Milestones Checklist (DMC), were compared in adjusted linear regression according to antiretroviral exposure. Results: Of 598 HEU children with valid neurodevelopment assessments, 382 were ART-exposed and 210 were ZDV-exposed. Adjusted mean Bayley-III scores were similar among ART-exposed vs. ZDV-exposed, with adjusted mean differences (95% confidence interval): Bayley-III Cognitive: −0.3 (−1.4, 0.9); Gross Motor: 0.8 (−0.1, 1.7); Fine Motor: 0.5 (−0.2, 1.3); Expressive Language: 0.7 (−0.3, 1.7); Receptive Language: 0.1 (−0.7, 0.8); and DMC Locomotor: 0.0 (−0.5, 0.6); Fine Motor: 0.3 (−0.3, 0.8); Language: −0.1 (−0.5, 0.4); Personal-Social: 0.2 (−0.7, 1.1). Similarly, when restricted to formula-fed children in one cohort (Tshipidi), there were no differences in adjusted mean scores. Conclusion: Neurodevelopmental outcomes at 24 months of age were similar in ART-exposed vs. ZDV-exposed HEU children. Maternal ART with breastfeeding does not appear to have an adverse effect on neurodevelopment. Abstract : Supplemental Digital Content is available in the text